Métodos de Calibração e Dosimetria de Aplicadores de Betaterapia - Trindade, Eduardo Mateus Motta [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The sources of betatherapy for clinical use in Brazil are, the vast majority of strontium-90, radioactive element that is not produced in the country, and therefore requires importation of international laboratories accredited by the International Atomic Energy Agency (IAEA).The use of these resources is always limited the crediting of characteristic values supplied by the manufacturer tables that provide the nominal value of activity and dose distribution to determine the irradiation time of the injury. The Institute of Nuclear Energy Research (IPEN / CNEN-SP) has recently researching the emission profile of these types of radiation sources, and some jobs are being developed with ionization chambers extrapolation for the purpose of standardizing a systematic calibration sources betatherapy. Other studies using parallel measures dosimeters (TLD's) and simulations with the Monte Carlo method. Radiological films have also been used in studies of applicators dosimetric analysis of strontium-90. This paper seeks to analyze the different methods for calibration of applicators betatherapy, already consolidated in studies by examining the advantages and disadvantages of each procedure

As fontes de betaterapia de uso clínico no Brasil são, em sua grande maioria, de estrôncio-90, elemento radioativo não produzido no país, e conseqüentemente requer importação de laboratórios internacionais credenciados pela Agência Internacional de Energia Atômica (AIEA).O uso destas fontes é sempre limitado a creditação de valores característicos fornecidos pelo fabricante, tabelas que fornecem o valor de atividade nominal e distribuição de dose para determinação do tempo de irradiação da lesão. O Instituto de Pesquisas Energéticas Nucleares (IPEN/CNEN-SP) vem recentemente pesquisando o perfil de emissão de radiação destes tipos de fontes, e alguns trabalhos estão sendo desenvolvidos com câmaras de ionização de extrapolação com a finalidade de se padronizar uma sistemática de calibração de fontes de betaterapia. Outros trabalhos paralelos com dosimetros termoluminescentes (TLD’s) e simulações com o método de Monte Carlo.Filmes radiológicos também têm sido utilizados em estudos de análise dosimétrica dos aplicadores de estrôncio-90. Neste trabalho pretende-se analisar os diferentes métodos propostos para calibração de aplicadores de betaterapia, já consolidados e em estudos, verificando as vantagens e desvantagens de cada um dos procedimentos
Keywords: Radiação; Radioterapia; Fisica medica